Cytokine patterns in nasal secretion of non-atopic patients distinguish between chronic rhinosinusitis with or without nasal polys. Issue 1 (December 2016) - König, Katrin; Klemens, Christine; Haack, Mareike; Nicoló, Marion; Becker, Sven; Kramer, Matthias; Gröger, Moritz
Abstract Background Being one of the most common nasal diseases, chronic rhinosinusitis (CRS) is subdivided into CRS with nasal polyps (NP) and CRS without nasal polyps (CRSsNP). CRSsNP presents itself with a TH 1 milieu and neutrophil infiltration, while NP is characterised by a mixed TH 1/TH 2 profile and an influx of predominantly eosinophils, plasma cells and mast cells. For the purpose of discovering disease-specific cytokine profiles, the present study compares levels of mediators and cytokines in nasal secretions between CRSsNP, NP, and healthy controls. Methods The study included 45 participants suffering from NP, 48 suffering from CRSsNP and 48 healthy controls. Allergic rhinitis constituted an exclusion criterion. Nasal secretions, sampled using the cotton wool method, were analysed for IL-4, IL-5, IL-10, IL-12, IL-13, IL-17, IL-8, GM-CSF, G-CSF, IFN-γ, MCP-1, MIP-1α, MIP-1β, eotaxin, and RANTES, and for ECP and tryptase, using Bio-Plex Cytokine assay or ELISA, respectively. Results Elevated levels of IL-5, IL-17, G-CSF, MCP-1, MIP-1α, MIP-1β, ECP, and tryptase, as well as decreased levels of IL-10, IL-12, IL-13, and IFN-γ were detected in NP. CRSsNP presented increased levels of RANTES and MIP-1β while IL-13 was decreased. No differences between the three groups were found for IL-4, IL-8, GM-CSF, and eotaxin. Conclusions The present work suggests a disequilibrium of TH 1 and TH 2, together with a down-regulation of regulatory T lymphocytes and up-regulated TH 17 in NP. Moreover, elevated levels of diverse mediators represent the activation of various inflammatory cells in this disease entity. The inflammation in CRSsNP, however, is only weakly depicted in nasal secretions. Therefore, cytokines in nasal secretions may provide helpful information for differential diagnosis.